An introduction to Digital Addressable Lighting Interface (DALI) systems & study of a DALI day lighting application - Meyer, Lisa (Kansas State University, 2007)
The DALI (Digital Addressable Lighting Interface) protocol has set forth the requirements for a digital fluorescent ballast that out performs its predecessors with respect to flexibility and functionality. The advantages of a DALI lighting control system range from advanced dimming capabilities and daylight sensing to saving money in energy and maintenance costs. A DALI lighting control system can also be beneficial to designers when trying to meet the requirements of code or recommended practices. The information in this report will help designers decide when to consider using a DALI lighting control system. This report covers topics such as the advantages of digitally addressable lighting, the equipment required to make a DALI system work, the limitations and drawbacks of DALI, cost information on installing and using a DALI system, and how DALI can help meet code and recommended practices, and concludes with a case study demonstrating how a DALI system has the potential to save money in energy costs.
Keywords: DALI; Digital addressable lighting interface; Lighting controls; Engineering, Electronics and Electrical (0544)